TANGGUNG JAWAB WALI BAPTIS DALAM PENDAMPINGAN IMAN ANAK DI PAROKI TIGALINGGA - Josep Sianturi; Petrus Simarmata; Timmi Malau (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
This study aims to analyze the understanding and implementation of the responsibilities of godparents in accompanying the faith development of children at the Parish of Saint Mary of Mount Carmel Tigalingga. This research employs a qualitative approach with a descriptive research design. Data were collected through observation, in-depth interviews, and documentation, involving godparents, godchildren, parents, and the parish priest as informants. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, using triangulation techniques to ensure data validity. The results of the study indicate that the implementation of godparents’ responsibilities in accompanying children’s faith development has not been optimal. In general, godparents do not provide personal guidance in the form of teaching prayers, catechesis, or nurturing the spiritual life of the child. Although godparents are actively involved in church life and demonstrate Christian values through their example, this is not accompanied by a personal relationship with the godchildren, resulting in an insignificant impact on the children’s faith development. Furthermore, the absence of structured formation programs from the parish contributes to the weak implementation of this role. In practice, children’s faith development is more influenced by the family and the church community. This study concludes that there is a gap between the Church’s teaching regarding the responsibilities of godparents and its implementation in practice. Therefore, continuous formation for godparents and the strengthening of personal relationships with godchildren are necessary to ensure effective faith accompaniment. ABSTRAK Penelitian ini bertujuan untuk menganalisis pemahaman dan pelaksanaan tanggung jawab wali baptis dalam pendampingan iman anak di Paroki Santa Perawan Maria dari Gunung Karmel Tigalingga. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data diperoleh melalui observasi, wawancara mendalam, dan dokumentasi dengan melibatkan wali baptis, anak baptis, orang tua, serta pastor paroki sebagai informan. Analisis data dilakukan melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan dengan menggunakan teknik triangulasi untuk menjamin keabsahan data. Hasil penelitian menunjukkan bahwa pelaksanaan tanggung jawab wali baptis dalam pendampingan iman anak belum berjalan secara optimal. Wali baptis umumnya tidak melakukan pendampingan secara personal dalam bentuk pengajaran doa, katekese, maupun pembinaan kehidupan iman anak. Meskipun wali baptis aktif dalam kehidupan menggereja dan memberikan keteladanan hidup Kristiani, hal tersebut tidak diiringi dengan relasi personal dengan anak baptis sehingga tidak berdampak signifikan terhadap perkembangan iman anak. Selain itu, tidak adanya program pembinaan yang terstruktur dari pihak paroki turut memengaruhi lemahnya pelaksanaan peran tersebut. Dalam praktiknya, perkembangan iman anak lebih banyak dipengaruhi oleh keluarga dan komunitas gereja. Penelitian ini menyimpulkan bahwa terdapat kesenjangan antara ajaran Gereja mengenai tanggung jawab wali baptis dan pelaksanaannya di lapangan. Oleh karena itu, diperlukan pembinaan yang berkelanjutan bagi wali baptis serta penguatan relasi personal dengan anak baptis agar pendampingan iman dapat terlaksana secara efektif.